2002
DOI: 10.1055/s-2002-19703
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Surgical Treatment of Brachial Plexus Injuries Using Nerve Grafting and Nerve Transfers

Abstract: Between 1993 and 1998, 32 male patients with brachial plexus injuries were surgically treated. Eighteen interfascicular grafting and 71 extraplexal neurotization procedures were performed separately or in combination. Donor nerves were the intercostals, spinal accessory, phrenic, contralateral C7, and cervical plexus, in order of frequency. Patients were followed for a minimum of 24 (average, 35) months. Biceps function was best following grafting the musculocutaneous nerve itself, or neurotization with the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0
9

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(79 citation statements)
references
References 19 publications
4
66
0
9
Order By: Relevance
“…Subsequently, several authors have reported their experience with intercostal nerve transfer [4,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] . In order to restore maximum function of the arm, as many intercostal nerves as possible are harvested and transferred.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, several authors have reported their experience with intercostal nerve transfer [4,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] . In order to restore maximum function of the arm, as many intercostal nerves as possible are harvested and transferred.…”
Section: Discussionmentioning
confidence: 99%
“…These studies comprise only 75 patients overall. 1,5,7,9,10,21,25 The differing results are shown in Table 5. Results of a metaanalysis 21 indicated that the accessory nerve-suprascapular nerve transfer is an effective repair technique; however, the indications for surgery in the various studies differed, and the results were not analyzed or presented uniformly.…”
Section: Nerve Transfermentioning
confidence: 99%
“…We do not consider this type of postoperative function a result of the surgical procedure. 10 Second, we reported on a selected group of upper plexus lesions, in which cases involving with a distally located brachial plexus lesion affecting shoulder function were excluded. Recovery after nerve repair is better in the latter group because of the absence of root avulsion and a shorter distance of the lesion to the target muscle.…”
Section: Neurosurg Focus / Volume 16 / May 2004mentioning
confidence: 99%
See 1 more Smart Citation
“…Todas ellas mostraron resultados favorables, con aproximadamente un 50% de reinervación del bíceps, y una fuerza M3 o más en la escala BMRC. Más recientemente, otras series han sido publicadas confirmando que esta técnica también es útil en niños con parálisis obstétrica del plexo braquial 13,27,35,49,58,68 . Los axones de cada nervio intercostal se reducen en número en un 10% cada 10 cm de longitud, a medida que van inervando en su recorrido la musculatura inspiratoria accesoria 49 .…”
Section: Nervios Intercostalesunclassified